Coherence and Cohesion: An Analysis of Students’ Narrative Paragraphs - Fitriani, Vina (STKIP AGAMA HINDU SINGARAJA, 2024)
This research is intended to examine aspects of coherence and cohesion in paragraphs written by class IX students at MTs Hasanudin Klungkung. In an effort to achieve research targets, a parallel convergent mixed methods approach was used, which allows the integration of qualitative and quantitative data. The data collection method used is cluster random sampling, where several classes are selected randomly from the entire population of classes at the MTs. The data collected was in the form of student writing, which was analyzed using qualitative and quantitative approaches. The results of the analysis show that students are able to display adequate coherence in their narrative paragraphs. They also use appropriate cohesive techniques to link ideas together, producing a cohesive paragraph as a whole. As a result, lessons that focus on coherence and cohesion are expected to improve the overall quality of students' writing.